Achievement goals, competition appraisals, and the well- and ill-being of elite youth soccer players over two competitive seasons - Adie, J. W.; Duda, J. L.; Ntoumanis, N. (Journal of Sport & Exercise Psychology, 2010)
Grounded in the 2 × 2 achievement goal framework (Elliot & McGregor, 2001), the purpose of this study was to investigate the temporal relationships between achievement goals, competition appraisals and indices of psychological and emotional welfare among elite adolescent soccer players. A subsidiary aim was to ascertain the mediational role of competition appraisals in explaining the potential achievement goal and well-/ill-being relationships. Ninety-one boys (mean age = 13.82 years) involved in an elite soccer program completed multisection questionnaires capturing the targeted variables. Measures were obtained on five occasions across two competitive seasons. Multilevel regression analyses revealed that MAp goals positively, and MAv goals negatively, predicted within-person changes in well-being over two seasons. PAp goal adoption was positively associated to within-person changes in negative affect. PAv goals corresponded negatively to between-person mean differences in positive affect. The results of the indirect effects showed challenge appraisals accounted for within-person associations between a MAp goal focus and well- and ill-being over time. The present findings provide only partial support for the utility of the 2 × 2 achievement goal framework in predicting young athletes` psychological and emotional functioning in an elite youth sport setting.